Sovereignty of natural resources and accountability. The case of the Bolivian hydrocarbon policy, 2006-2018 - César Augusto Camacho-Soliz (Íconos)
This article analyzes the Bolivian hydrocarbon public policy of the 2006-2018 period, drawing from the analytical framework of public policy designs and the methodological accounts of tracing processes. This research seeks to understand the formulation and implementation of specific types of extractivist public policies in democratic contexts. The objective is to highlight how the sovereign recovery of natural resources generates public responsibility deficits. In order to address this topic, a causal mechanism, that includes the analysis of the adoption of new policy objectives (placed on the agenda), is identified and established, as well as the description of the means of the policy (formulation), its adaptation to the existing rules (institutional change) and the way in which the instruments are measured and combined at the time of implementation (political interaction) to generate the expected result. Finally, each aspect of the causal mechanism is supported by empirical evidence obtained through the identification of policy instruments organized in a research protocol under the NATO (Nodality, Authority, Treasure and Organization) typology in order to provide external and internal validation for the hypothesis. Bolivia is selected from a set of typical cases with the selection criteria centered on the relationship between the proposed cause and expected effect.